Digital elevation model of spit using DInSAR of radarsat-1 fine mode data - Marghany, Maged (2012)
This work presents a new approach for 3-D object simulation using Deferential synthetic aperture interferometry (DInSAR). In doing so, new approach of using fuzzy B-spline algorithm is implemented with phase unwrapping technique. Consequently, fuzzy B-spline is used to eliminate the phase decorrelation impact from the interferograms. The study shows the performance of DInSAR method using fuzzy B-spline is better than DInSAR technique which is validated by a lower range of error (0.02 ±0.21m) with 90% con?dence intervals. In conclusion, integration of fuzzy B-spline with phase unwrapping produce accurate 3-D coastal geomorphology reconstruction.